Essential University Physics: Volume 1 (4th Edition) Clone

Published by Pearson
ISBN 10: 0-134-98855-8
ISBN 13: 978-0-13498-855-9

Chapter 4 - Exercises and Problems - Page 72: 64

Answer

The proofs are below.

Work Step by Step

a) We know that the force is: $F=k_tx$ In parallel, the spring constant is additive, so $k_t=k_1+k_2$. Thus: $F=(k_1+k_2)x$ b) We know that the force is: $F=k_tx$ In series, we can find $k_t$ to be: $\frac{1}{k_t}=\frac{1}{k_1}+\frac{1}{k_2}$ $\frac{1}{k_t}=\frac{k_1+k_2}{k_1k_2}$ $k_t=\frac{k_1k_2}{k_1+k_2}$ Thus, the force is: $F=(\frac{k_1k_2}{k_1+k_2})x$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.